2011
DOI: 10.1111/j.1708-8305.2010.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Etiology, and Determinants Associated With Acute Diarrhea Among French Forces Deployed to Chad

Abstract: This study found a high frequency of enteric viruses and a high risk of person-to-person transmission associated with diarrhea. Eating at the military mess or staying in a temporary encampment conferred a protective effect. In addition to food-borne disease prevention, stringent hygiene measures are required to break transmission of diarrhea during military deployments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…There are no previous reports of TD in tourists to Benin, and very few of travellers to West Africa [8,10-13] One of the noteworthy findings was the exceptionally high incidence of TD among our study subjects. Although Sub-Saharan Africa is generally presented as an area with a 20 – 60% risk for TD [17-20], 87% of our travellers reported having contracted the disease.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…There are no previous reports of TD in tourists to Benin, and very few of travellers to West Africa [8,10-13] One of the noteworthy findings was the exceptionally high incidence of TD among our study subjects. Although Sub-Saharan Africa is generally presented as an area with a 20 – 60% risk for TD [17-20], 87% of our travellers reported having contracted the disease.…”
Section: Discussioncontrasting
confidence: 48%
“…No cases with Vibrio cholerae , Yersinia or Campylobacter were found. Campylobacter, although common in Southeast Asia and Nepal [3,5,23,24], has not been considered a major pathogen in West Africa in previous reports either [8,10-13,24]. Vibrio cholerae and Yersinia are rare in TD everywhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most travelers (83 %) reported at least one episode of TD, without reduction in episodes as travel durations lengthened. Another cross-sectional study of long-term backpackers in Thailand reported that a longer stay was associated with having [26,27]. Both studies cite living in close quarters (facilitating person-to-person transmission of enteric pathogens) and the consumption of food purveyed by off-base local vendors as risk factors.…”
Section: Diarrheal Diseasementioning
confidence: 99%